Search for Dust Emission from (24) Themis Using the Gemini-North Observatory. (26th June 2018) - Hsieh, Henry H.; Kim, Yoonyoung; Fitzsimmons, Alan; Sykes, Mark V.
Abstract: We report the results of a search for a dust trail aligned with the orbit plane of the large main-belt asteroid (24) Themis, which has been reported to have water ice frost on its surface. Observations were obtained with the GMOS instrument on the Gemini-North Observatory in imaging mode, where we used a chip gap to block much of the light from the asteroid, allowing us to take long exposures while avoiding saturation by the object. No dust trail is detected within 2′ of Themis to a 3- σ limiting surface brightness magnitude of Σlim ∼ 29.7 mag arcsec −2, as measured along the expected direction of the dust trail. Detailed consideration of dust ejection physics indicates that particles large enough to form a detectable dust trail were unlikely to be ejected as a result of sublimation from an object as large as Themis. We nonetheless demonstrate that our observations would have been capable of detecting faint dust emission as close as 20″ from the object, even in a crowded star field. This approach could be used to conduct future searches for sublimation-generated dust emission from Themis or other large asteroids closer to perihelion than was done in this work. It would also be useful for deep imaging of collisionally generated dust emission from large asteroids at times when the visibility of dust features are expected to be maximized, such as during orbit plane crossings, during close approaches to the Earth, or following detected impact events.